(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article, the educational system, which is considered the basis of New Uzbekistan, the political changes carried out by our country, and the goals of training qualified staff and obtaining a competitive intelligent resource in accordance with international standards are revealed. The article emphasizes conducting educational activities based on humanitarianism.